2018
DOI: 10.1038/s41426-018-0187-x
|View full text |Cite
|
Sign up to set email alerts
|

Filamentation in Candida auris , an emerging fungal pathogen of humans: passage through the mammalian body induces a heritable phenotypic switch

Abstract: Morphological plasticity has historically been an indicator of increased virulence among fungal pathogens, allowing rapid adaptation to changing environments. Candida auris has been identified as an emerging multidrug-resistant human pathogen of global importance. Since the discovery of this species, it has been thought that C. auris is incapable of filamentous growth. Here, we report the discovery of filamentation and three distinct cell types in C. auris: typical yeast, filamentation-competent (FC) yeast, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
189
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(197 citation statements)
references
References 41 publications
4
189
1
3
Order By: Relevance
“…Several conditions, which induce hyphal growth in C. albicans, such as incubation at 37 °C, and Lee's medium at pH3.5 or pH6.5, as well as media containing serum, isoamyl alcohol, or bleocin, were tested, but none of these triggered filamentous growth in the S. Asian (clade I) C. auris strain UACa11 (data not shown) (15). Likewise, growth at 25 °C did not produce filaments as described previously for a C. auris clinical isolate (21). However, using strain UACa11, we observed filamentous growth in the presence of sublethal concentrations of genotoxic drugs affecting DNA replication progression or inducing DNA damage (HU, MMS, and 5-FC) ( Fig.…”
Section: Auris Produces Pseudohyphae Under Genotoxic Stressmentioning
confidence: 72%
“…Several conditions, which induce hyphal growth in C. albicans, such as incubation at 37 °C, and Lee's medium at pH3.5 or pH6.5, as well as media containing serum, isoamyl alcohol, or bleocin, were tested, but none of these triggered filamentous growth in the S. Asian (clade I) C. auris strain UACa11 (data not shown) (15). Likewise, growth at 25 °C did not produce filaments as described previously for a C. auris clinical isolate (21). However, using strain UACa11, we observed filamentous growth in the presence of sublethal concentrations of genotoxic drugs affecting DNA replication progression or inducing DNA damage (HU, MMS, and 5-FC) ( Fig.…”
Section: Auris Produces Pseudohyphae Under Genotoxic Stressmentioning
confidence: 72%
“…How could a single amino acid change in this insert region affect filamentation or other processes that require the efficient functioning of the Flo8 as a transcriptional activator? If filamentation benefits the AmB‐insulted fungus by helping it to protect itself from the action of AmB, as appears to be the case for C. albicans , and if the passage‐mediated increase in filamentation or filamentation competence is also an adaptive or beneficial step for the fungus, then a Flo8 S → N mutation found precisely in an AmB‐resistant strain would suggest an increase, rather than a decrease, in filamentation or filamentation competence, and thus possibly an increase in the net efficiency of transcription events that promote such properties.…”
mentioning
confidence: 99%
“…These reasons include, for example, the observation that filamentation is linked to Flo8 or FLO genes, and that a strategy involving filamentation and/or filamentation competence could be employed by C. auris for its survival/virulence within the host and/or for its resistance to antifungal drugs. Indeed, it has been observed that passage through the host organism favors a heritable switch of C. auris to a filamentous or filamentation‐competent form . Correspondingly, in the congeneric species Candida albicans , experimental results strongly suggest that filamentation protects the yeast cells against programmed cell death induced by the antifungal drug amphotericin B (AmB) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, sea birds may serve as reservoirs for indirect transmission of drug resistant Candida species, such as C. glabrata , to humans (24). The uncanny ability of C auris for niche-specific adaptations, first in the environment, then in an avian host might have led as a third step to the ultimate establishment as a human pathogens through genetic and epigenetic switches (25). The hypothesis that C. auris broke the mammalian thermal barrier through adaptation to climate change suggests several experimental lines of investigation to obtain evidence for and against it.…”
mentioning
confidence: 99%